Real-World Prevalence of Direct Oral Anticoagulant Off-Label Doses in Atrial Fibrillation: An Epidemiological Meta-Analysis - Shen, Nan-Nan; Zhang, Chi; Hang, Ying; Li, Zheng; Kong, Ling-Cong; Wang, Na; Wang, Jia-Liang; Gu, Zhi-Chun (Frontiers in Pharmacology, 2021)
Background: The use of direct oral anticoagulants (DOACs) off-label doses in atrial fibrillation (AF) patients may result in poor clinical outcomes. However, the true prevalence remains scarce. This study aims to estimate the prevalence of DOACs off-label doses in AF patients. Methods: Databases of MEDLINE, EMBASE, and COCHRANE were searched through February 2020 for real-world studies that reported off-label definition and prevalence data of AF patients using DOACs. The primacy outcomes were overall prevalence of DOACs off-label doses, and corresponding under-dose and over-dose. Random-effects model was used for data synthesis. Variations on individual DOAC and different regions were examined by subgroup analyses. Results: A total of 23 studies involving 162,474 AF patients were finally included. The overall prevalence of DOACs off-label doses was 24% (95% CI, 19%-28%), with 18% for dabigatran, 27% for rivaroxaban, 24% for apixaban, and 26% for edoxaban. The prevalence of under-dosed DOACs was 20% (95% CI, 16%-24%), with significant difference among individual anticoagulant (13% for dabigatran; 22% for rivaroxaban; 22% for apixaban; 18% for edoxaban; Pinteraction=0.02). The prevalence of over-dosed DOACs was 5% (95% CI, 3%-7%), with lowest prevalence observed in apixaban (2%). Subgroup analyses by regions demonstrated that prevalence of DOACs off-label doses was higher in Asia (32%) than in North America (14%) and in Europe (22%), with under-dose predominant. Regardless of different regions, prevalence of over-dose was relatively low (4%-6%). Conclusions: This study provides an estimation of DOACs off-label doses in real-world setting. The prevalence rate of DOACs off-label doses in AF patients was relatively high, with under-dose predominant. Clinician in Asian preferred to prescribe under-dose of DOACs to AF patients. More evidence about the appropriateness of DOACs off-label doses in AF patients is urgently needed. The education programs concerning the appropriate prescriptions of DOACs within the drug labels and accepted guidelines are necessary to DOACs prescribers to ensure the safety and effectiveness of anticoagulation therapy for patients with AF.